Educational innovation and COVID-19: the crisis as a challenge and opportunity Abstract (Revista INTEREDU11, 2023)
COVID-19 has renewed the forces for the transformation of education through the promotion of educational innovation, and, in the seek to raise evidence on such processes, several investigations have emerged in the form of reports and presentations of results which have not been published in academic journals to evidence such situation. In this context, the objective of this article has been to systematize the educational innovations that have emerged during the pandemic and their main challenges, together with opportunities in their best conditions for sustainability. This research has been carried out under a qualitative methodology, and has been based on the study of a documentary review, 14 publications prepared by research centers, NGOs, and foundations focused on the educational field, in Chile, between March 2020 and June 2022. The results highlight the proliferation of didactic, curricular, and above all, technological innovations, as well as their challenges and opportunities. Thus, teacher training appears to be a new challenge, plus the involvement of students and parents, hand in hand with such resource; while opportunities include collaborative work, networking, leadership, government support, as well as to accept the ownership of innovation.
Keywords: Education; distance education; educational innovation; pandemic; Chile